INTEGRATING AI-POWERED TOOLS FOR DEVELOPING WRITING SKILLS IN EFL CLASSES - A.Ashurov (TADQIQOTLAR, 2026)
Annotation This article explores the role of AI-powered tools in developing writing skills in EFL  classes.  It  explains  how  tools  such  as  ChatGPT  and  Grammarly  can  support learners in brainstorming, drafting, revising, and correcting their written work. The article also discusses the primary benefits and potential challenges of utilizing AI in writing instruction. The study concludes that AI tools are most effective when they are used under teacher guidance and for clear educational purposes.